1989
DOI: 10.1099/00221287-135-3-629
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glutamine Synthetase Isoenzymes in Rhizobium leguminosarum biovar viceae

Abstract: Ammonia assimilation in Rhizobium leguminosarum biovar viceae strain RCRlOO 1 (hereafter called R . leguminosarum) appears to take place only through the glutamine synthetase/glutamate synthase pathway since (a) no glutamate dehydrogenase was detected in crude extracts of bacteria grown in different nitrogen sources, and (b) the growth rate on glutamine as a nitrogen source was faster than that observed on NH4Cl. In contrast to reports for other Rhizobium species, R . leguminosarum can definitely utilize NH4C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 20 publications
1
25
0
2
Order By: Relevance
“…1. viceae LPRllO5, a rifampicinresistant derivative of strain RCRlOOl (Hooykaas eta/., 1977). Growth conditions and preparations of cell extracts were as described previously (Rossi et al, 1989). Protein concentration was determined by the Bio-Rad protein assay using bovine serum albumin (BSA fraction V, Sigma) as a standard.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1. viceae LPRllO5, a rifampicinresistant derivative of strain RCRlOOl (Hooykaas eta/., 1977). Growth conditions and preparations of cell extracts were as described previously (Rossi et al, 1989). Protein concentration was determined by the Bio-Rad protein assay using bovine serum albumin (BSA fraction V, Sigma) as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that transferase activity of GSII assayed in crude extracts, is rapidly removed after addition of NH,Cl to a culture derepressed for GSII (Bravo & Mora, 1988;Fuchs & Keister, 1980;Howitt & Gresshoff, 1985 ;Ludwig, 1980). Addition of chloramphenicol prior to NH,Cl prevents disappearance of GSII transferase activity (Rossi et al, 1989). This phenomenon may be interpreted in several ways, as, for example, accumulation of an inhibitor or degradation of the enzyme; furthermore, a correlation with enzyme dilution following repression has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations